Jiangtang Sanhao formula ameliorates skeletal muscle insulin resistance via regulating GLUT4 translocation in diabetic mice - Ye, Zimengwei; Ma, Jinkun; Liu, Yage; Xu, Bingrui; Dai, Xuan; Fu, Min; Tian, Tian; Sui, Xin; Mo, Fangfang; Gao, Sihua; Zhao, Dandan; Zhang, Dongwei (Frontiers in Pharmacology, 2022)
Jiangtang Sanhao formula (JTSHF), one of the prescriptions for treating the patients with diabetes mellitus (DM) in traditional Chinese medicine clinic, has been demonstrated to effectively ameliorate the clinical symptoms of diabetic patients with overweight or hyperlipidemia. The preliminary studies demonstrated that JTSHF may enhance insulin sensitivity and improve glycolipid metabolism in obese mice. However, the action mechanism of JTSHF on skeletal muscles in diabetic mice remains unclear. To this end, high-fat diet (HFD) and streptozotocin (STZ)-induced diabetic mice were subjected to JTSHF intervention. The results revealed that JTSHF granules could reduce food and water intake, decrease body fat mass, and improve glucose tolerance, lipid metabolism, and insulin sensitivity in the skeletal muscles of diabetic mice. These effects may be linked to the stimulation of GLUT4 expression and translocation via regulating AMPKα/SIRT1/PGC-1α signaling pathway. The results may offer a novel explanation of JTSHF to prevent against diabetes and IR-related metabolic diseases.